Biodegradation pathway prediction of pops of POPS (Persistent Organic Pollutants) and biobarrier treatment. (2010)
In this paper, the biodegradation pathway of Dieldrin is simulated using an expert system. This insecticide is included in the Stockholm Convention, signed and ratified by Colombian government in 2008, and it is considered one of the most harmful humanmade compounds. For this model contaminant a complete metabolic biodegradation sequence was built and a simulationbased strategy was formulated for its biodegradation in a practical case. According to the simulated metabolic pathway, a sequential aerobicanaerobicaerobic reactor would be the best choice to achieve complete biodegradation. Using these results, the authors propose an innovative system for the biological treatment of POPs; this system was called BioReactive Permeable Barrier (BioBarrier). In this work a description of the main and fundamentals aspects of BioBarrier system is also included, showing a new and potential possibility for the biotreatment of hazardous pollutants.